A multicentre cross-sectional survey of the core competence of paediatric emergency nurses - Tao, Yi; Li, Wenjing; Zhang, Li; Zhan, Shuang; Wang, Man; Feng, Mei (Frontiers in Pediatrics, 2025)
IntroductionTo understand the core competency levels of paediatric emergency nurses and factors that influence these levels, and to provide a basis for improving the core competencies of paediatric emergency nurses via education and training, and to provide a reference for managers for implementing scientific management models.MethodsFrom October to November 2022, convenience sampling was used to select 540 paediatric emergency nurses from 9 provinces and cities across the country as survey subjects. A self-designed “Self-evaluation questionnaire on core competencies of paediatric emergency nurses” was used for survey analysis.ResultsThe average score of the core competency items among paediatric emergency nurses was 4.06 ± 0.74, the highest score was 4.51 ± 0.62 in the professional attitude dimension, and the lowest score was 3.70 ± 0.81 in the professional development ability dimension. The results of the multiple regression analysis revealed that the hospital level and emergency management experience are the factors that influence the core competencies of paediatric emergency nurses. The core competencies of paediatric emergency nurses are at an average level and are influenced by various factors.DiscussionPaediatric emergency nursing managers should develop comprehensive, systematic, and professional training plans, implement scientific management models in paediatric emergency management work, and increase the core competency levels of paediatric emergency nurses.